Pendekatan Syariah dalam Menggalakkan Amalan Hijau melalui Dana Zakat: Satu Kajian Awal: Shariah Approach in Promoting Green Practices through Zakat Fund: A Preliminary Study - Arsad, Muhammad Ilhamuddin; Jamaludin, Hafiz; Samudin, Siti Aisyah (Al-Basirah Journal, 2024)
Climate change and environmental degradation are major global challenges that require holistic solutions. In the context of Islam, zakat as a unique financial instrument has great potential to support sustainability efforts through the promotion of green practices. This article examines how the sharia approach can be used to leverage zakat funds in promoting green initiatives. This study uses a qualitative methodology through the analysis of relevant literature and compares it with the Islamic legal framework. The results of the study show that zakat funds can be used to support sustainability projects such as environmental conservation, natural resource management and green awareness education. This article concludes that zakat can play an important role in addressing climate change by ensuring its use is in line with sharia principles.